2017
DOI: 10.1002/gj.2941
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and tectonic setting of the Shiduolong skarn Pb–Zn deposit in the East Kunlun Orogenic Belt: Constraints from whole‐rock geochemical, zircon U–Pb and Hf isotope analyses

Abstract: The Shiduolong Pb–Zn deposit, located in the East Kunlun Orogenic Belt, is a medium‐scale skarn deposit (0.4 Mt metal reserves with a grade of 1.46% Pb and 4.38% Zn). The mineralization occurs along the contact zone between Carboniferous marbles and Triassic quartz diorite and granodiorite. Zircon LA‐ICP‐MS dating indicates that the Shiduolong quartz diorite is coeval with the granodiorite (245 Ma). Whole‐rock geochemical analysis shows that both phases are high‐K calc‐alkaline metaluminous (A/CNK < 1) I‐type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In the Late Triassic, with the progressive closure of the A'nyemaqen Ocean, the E-KOB and BH-SG collided with each other, ultimately forming the Palaeo-Tethys ophiolite mélange belt (A'nyemaqen ophiolite mélange belt, Ding et al, 2011;Hu et al, 2016, Figure 1). A large number of previous studies have shown that the E-KOB experienced a largescale mantle-derived magmatic underplating event during the Mid-Triassic (Li et al, 2012;Shao et al, 2017;Wu et al, 2020;Xin et al, 2019;Xiong et al, 2016;Zhong, Feng, Seltmann, Dolgopolova, Andersen, et al, 2018); in this period, the eastern E-KOB indicates an extensional tectonic regime accompanied by amounts of calc-alkaline magmatism (Figure 6c,d), specifically expressed as the eruption of a large number of mafic-intermediatefelsic magmatic rocks Shao et al, 2017;Wang et al, 2018;Xia et al, 2015;Xia et al, 2017;Xin et al, 2019). The presence of extensive magmatism is clearly also considered a product of Palaeo-Tethys plate subduction (Xia et al, 2017;Xin et al, 2019).…”
Section: Tectonic Setting and Geological Significancementioning
confidence: 94%
See 3 more Smart Citations
“…In the Late Triassic, with the progressive closure of the A'nyemaqen Ocean, the E-KOB and BH-SG collided with each other, ultimately forming the Palaeo-Tethys ophiolite mélange belt (A'nyemaqen ophiolite mélange belt, Ding et al, 2011;Hu et al, 2016, Figure 1). A large number of previous studies have shown that the E-KOB experienced a largescale mantle-derived magmatic underplating event during the Mid-Triassic (Li et al, 2012;Shao et al, 2017;Wu et al, 2020;Xin et al, 2019;Xiong et al, 2016;Zhong, Feng, Seltmann, Dolgopolova, Andersen, et al, 2018); in this period, the eastern E-KOB indicates an extensional tectonic regime accompanied by amounts of calc-alkaline magmatism (Figure 6c,d), specifically expressed as the eruption of a large number of mafic-intermediatefelsic magmatic rocks Shao et al, 2017;Wang et al, 2018;Xia et al, 2015;Xia et al, 2017;Xin et al, 2019). The presence of extensive magmatism is clearly also considered a product of Palaeo-Tethys plate subduction (Xia et al, 2017;Xin et al, 2019).…”
Section: Tectonic Setting and Geological Significancementioning
confidence: 94%
“…The major and trace element compositions of the DHB volcanic rocks are listed in Table S3. The samples of the volcanic rocks (RCT and RWT) numerous precise geochronologic ages (Liu et al, 2012;Ren et al, 2016;Shao et al, 2017;Wang et al, 2016;Wang et al, 2018;Wu et al, 2020;Xia et al, 2015;Xia et al, 2017;Xin et al, 2019). As mentioned earlier, both the Xilikete Formation and Elashan Formation at the eastern margin of the E-KOB contain volcaniclastic rocks.…”
Section: Whole-rock Major and Trace Element Geochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Many porphyry-skarn deposits have been discovered and explored in this area (e.g., the Kaerqueka Cu-Mo porphyry deposit, Hutouya Cu-Pb-Zn skarn deposit, and Galinge Fe skarn deposit [9][10][11][12][13]). Many publications have focused primarily on the geochemistry of the granite [14][15][16][17][18] and on the description of the geological characteristics of typical deposits and their host rocks [19][20][21]. The mineralization age has also been investigated, yielding Re-Os dates of 226.5 ± 5.1 Ma [9] for the Shuangqing Fe deposit and 236.2 ± 2.1 Ma [22] for the Shenduolong Pb-Zn polymetallic deposit.…”
Section: Introductionmentioning
confidence: 99%